The International Conference on Information Network 2012 2012
DOI: 10.1109/icoin.2012.6164398
|View full text |Cite
|
Sign up to set email alerts
|

A deployable upload acceleration service for mobile devices

Abstract: As the number of smart phones and other mobile devices are proliferating, traffic volume generated by them grows drastically these days. These devices are often connected to WiFi access points (APs) for the first/last mile accesses to the Internet. APs accommodate large traffic to and from these mobile devices. While downloading large content onto mobile devices is often aided by caches placed at and near the WiFi APs, uploading large User-Generated-Content (UGC) has rarely been accelerated. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Many researchers have addressed the problem of uploading contents while considering the cache [23][24][25][26][27][28][29][30]. In [23], the authors proposed a mobile video uplink caching algorithm to increase video quality via recover lost video frame in real-time video transmission.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have addressed the problem of uploading contents while considering the cache [23][24][25][26][27][28][29][30]. In [23], the authors proposed a mobile video uplink caching algorithm to increase video quality via recover lost video frame in real-time video transmission.…”
Section: Related Workmentioning
confidence: 99%
“…The upload cache reduced user online time for uploading the content and reduced the peak traffic volume between edge networks and data centers. In [26], the authors designed an upload acceleration service framework for mobile devices on virtual network architecture host-based WiFi as the access point. That architecture is designed in threefolds: upload acceleration service to the designated flow of data, a two-tier architecture where UGC is first cached to the front-end, then to the back-end, finally to the internet.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, both [9] and [10] also divided the upload process in the same way as in [8] and placed cache at the nearby WiFi access points. Specifically, [9] demonstrated that larger contents could save more connection time for users. And [10] proposed a smart offloading mechanism for content uploading and considered the WiFi bandwidth scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…Then the authors in [8] proposed a upload cache scheme in edge networks to shorten the duration and reduce the peak traffic volume, by dividing the traditional upload process into two phases: from the client to the gateway cache and from the gateway to the destination server. In addition, both [9] and [10] also divided the upload process in the same way as in [8] and placed cache at the nearby WiFi access points. Specifically, [9] demonstrated that larger contents could save more connection time for users.…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies target on optimizing the last-mile delivery problem, i.e., from the CDN edge server to end user terminal [13], [14], [15]. For data upstream, which is mostly left unattended by legacy CDNs, there are few solutions for improving its performance [16].…”
Section: Introductionmentioning
confidence: 99%